Comparative Photocatalytic Performance of Gd, Zn, and Ti Metal Oxide Catalysts for Polyethylene Microplastics Removal - Mohammad Luqman, Ismail; Norzahir, Sapawe; Muhammad Farhan, Hanafi; Hairul Amani, Abdul Hamid; Siti Munirah, Sidik (Integrated Publishing Association, 2025)
This study presents a comparative analysis of the photocatalytic degradation efficiency of modified and commercial Gd₂O₃, ZnO, and TiO₂ metal oxide catalysts for the removal of polyethylene (PE) microplastics under controlled laboratory conditions. Among the tested catalysts, modified ZnO exhibited the highest degradation efficiency of 78% under optimum conditions: 10 ppm PE concentration, 3-4 g/L catalyst dosage, pH 7, visible light irradiation for 2 hours at 303 K. This was followed by modified Gd₂O₃ (68%) and modified TiO₂ (58%) under the same conditions. All modified catalysts outperformed their commercial counterparts, while the photolysis control experiment showed less than 5% degradation. The enhanced photocatalytic activity is attributed to improved charge separation, greater generation of reactive oxygen species (ROS), and increased surface adsorption capacity introduced by defect engineering and structural modifications. Negligible degradation in the absence of light confirms the dominance of photocatalytic mechanisms over photolysis or dark reactions. These findings underscore the potential of surface-modified ZnO as a highly effective catalyst for the remediation of microplastic pollution.